HISTOMORPHOLOGICAL AND BIOCHEMICAL STUDIES IN PLASMA AND LIVER OF FIELD RATS INHABITING SOUTH-WEST REGION OF PUNJAB IN NORTH INDIA - PARKASH SINGH; GURINDER KAUR SANGHA (The Bioscan, 2015)
The present study was designed to examine the possible effect of environmental contaminants on the biochemical constituents of field rats residing Bathinda district of Punjab. The amount of proteins and enzymes aminotransferases and phosphatases was low in plasma of male and female R. rattus, but higher in T. indica and B. bengalensis residing in Bathinda region as compared to control rats. Protein amount and levels of enzymes ALT, AST and ACP were higher in liver of Bathinda male and female R. rattus and T. indica. Pesticide residue of malathion was detected in liver sample of these rats. Slight loosening in arrangement of hepatic cords, infiltration of leucocytes, dilation in central vein (CV) and presence of pyknotic cells (PN) was observed in rats collected from Bathinda district. The environmental contaminants/pesticides may be responsible for the biochemical and histological alterations in field rats.of Bathinda.